Designing and evaluating tourism experiences in senior mobility: An application of the OEC framework - Marta Amaral; Ana Isabel Rodrigues; Alice Diniz; Sandra Oliveira; Susanal Leal (Tourism & Management Studies)
This research was developed in the frame of the VOLTO JÁ Project, which aims to implement a senior social exchange program in Portugal, among social economy organizations to promote tourism experiences for the elderly. The main goal of the research is to present a three-stage model of designing and evaluating tourism experiences in senior mobility, named as the OEC Model. This model was established based on a set of data collection instruments, which were chosen according to the goals of each stage of the process, in the context of the VOLTO JÁ Project. The results of stage one and three of the model considered as a more integrated approach on designing and evaluating senior tourism experiences are presented. The findings highlight the importance of a pre-stage in what concerns organizing the tourism experience (supply perspective); and a post-stage assessing senior´s perceptions after the experience (demand perspective).